2002
DOI: 10.1007/s00216-002-1281-3
|View full text |Cite
|
Sign up to set email alerts
|

On-line electrochemistry – MS and related techniques

Abstract: This review summarizes publications on the on-line coupling of electrochemistry with mass spectrometry. After a brief historic introduction it is divided into three parts, organized in order of increasing complexity of the experimental arrangement. The first section deals with the use of the electrospray ion source as an electrochemical reactor for oxidation or reduction reactions. It is followed by the second part which covers the hyphenation of different kinds of electrochemical flow cell with a variety of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
58
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 89 publications
0
58
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15] It has also been reported that an electrochemical reaction coupled on-line to LC-MS is a promising approach in drug metabolism and protein research. [16][17][18][19][20][21][22][23] However, there are few reports on applications to methods for determining organic compounds in biological samples using this technique.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] It has also been reported that an electrochemical reaction coupled on-line to LC-MS is a promising approach in drug metabolism and protein research. [16][17][18][19][20][21][22][23] However, there are few reports on applications to methods for determining organic compounds in biological samples using this technique.…”
Section: Introductionmentioning
confidence: 99%
“…, it is generally accepted that redox reactions do occur in the capillary sprayers and that they are responsible for charge balance [1,2]. Redox processes in electrospray mass spectrometry were comprehensively investigated by and, more recently, electrochemical aspects and applications of electrospray ionization were the focus of reviews [9,10].Ions formed by one electron reduction from nonmetallated dicationic species in solution were previously observed in positive-mode electrospray mass spectrometry for ionic compounds such as diquaternary pyridinium salts [11-13] and free-base N-alkylpyridiniumyl porphyrin salts [14]. One-and two-electron reductions of the cations of metallated N-alkylpyridiniumyl porphyrin salts were also reported, when electrospray was used in the positive mode [15][16][17].…”
mentioning
confidence: 99%
“…, it is generally accepted that redox reactions do occur in the capillary sprayers and that they are responsible for charge balance [1,2]. Redox processes in electrospray mass spectrometry were comprehensively investigated by and, more recently, electrochemical aspects and applications of electrospray ionization were the focus of reviews [9,10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Early experiments with ESI in our laboratory failed to produce abundant molecular ions suitable for quantification and confirmation by MRM. These results were not unexpected because alcohols do not normally protonate or deprotonate extensively during the ESI or APCI°process° [35] In addition to [BHETME ϩ O 2 ] Ϫ at m/z 230, the negative ion mass spectrum of BHETME exhibited an ion at m/z 200 as well as other ions of the same m/z as those present in the mass spectrum of the analogous sesqui-mustard°hydrolysis°product°BHETM°(Table°1). Ϫ derived from BHETME.…”
Section: Resultsmentioning
confidence: 85%